THE ESTABLISHMENT OF GEREJA KRISTEN JAWI WETAN (GKJW) TUNJUNGREJO YOSOWILANGUN SUBDISTRICT LUMAJANG - Ismaul Fitroh (Journal of Social Studies (JSS), 2017)
Tunjungrejo is one of the unique village located in the region of Lumajang. The uniqueness of the village can be seen in the presence of Protestant religion. Other uniqueness are their house of worship, namely Gereja Kristen Jawi Wetan (GKJW). Brontodiwirjo has an important role to the development of Protestant in Tunjungrejo. Brontodiwirjo as forest loggers Tunjungrejo is also a teacher of the gospel in this region. Along Tunjungrejo forest clearing, many newcomers who are Christians and non Christians. To maintain the existence of Protestant Christianity, Brontodiwirjo as forest loggers Tunjungrejo apply the rule that people who want to settle in the region Tunjungrejo be Protestant. From this Tunjungrejo society formed by the belief in one religion. As a result of the continued development of the Protestant Christian church he built a house of worship that is GKJW Tunjungrejo.Keywords: Gereja Kristen Jawi Wetan (GKJW), Tunjungrejo, Brontodiwirjo.